A Systematic Review of Biomedical and Psychosocial Factors for Suicide: An Islamic Perspective - Kitota, Abdillah Mussa (Journal of Quranic Sciences and Research, 2023)
Suicide is a complex public health problem of global dimension with un-even distribution rates. The objectives of this review is to describe the concept of suicide, its causes and preventive measures in the light of the glorious Qur’an and ahadith/sunnah as the principal sources of Maqasid Al-Shari’ah in Islam. Descriptive study design was used to review the data collected from published articles, books, news and reports. The findings show that suicide may be caused by social-economic factors; catalysed by psychological problems, mental illnesses, physical illnesses, genetics and medication. Qur’an, 4:29 has strictly forbidden people to kill themselves, while various ahadith have made it clear that whoever kills himself with something, Allah (Subhaanahu wata’alah) will punish him with whatever he has killed himself with in the Hell-fire. The guidelines to prevent suicide include strengthening personal relationships, reciting and comprehending the glorious Qur’an, supplication, ruqya, patience and reliance to Allah (S.W.T).